ACCOUNT RECEIVABLES INFORMATION SYSTEM FOR ELECTRICAL PRINTING PLN SERVICE UNIT CILEDUG USING VISUAL BASIC 6.0 - Siti Meitri Rigiyani; Aqwam Rosadi Kardian, Skom, MM (Jurnal Sistem Informasi, 2004)
this includes all processes. Understanding was the thing mutlask required to plan anew system. In this study, the authors explain the conversion of old systems to newsystems using Visual Basic 6.0.With the new system is expected to errors in entering data can be reduced, so thatwhen the process does not have problems. Jobs in making statements on a monthlybasis can be done in a timely manner and not dull in its execution. Data andinformation obtained is always in a state of accurate so that the use of computers canbe more efficient and effective and can save substantial operating costs.